2008
DOI: 10.1002/hup.958
|View full text |Cite
|
Sign up to set email alerts
|

Effects of warm‐supplementing kidney yang (WSKY) capsule added on risperidone on cognition in chronic schizophrenic patients: a randomized, double‐blind, placebo‐controlled, multi‐center clinical trial

Abstract: WSKY capsule added on risperidone may improve cognitive function, social function of the chronic schizophrenic patients, and the WSKY safely during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Similarly, herbal and natural medicines are also in the early phase of testing but have produced some promising results. Warm-supplementing kidney yang, a Chinese herbal medicine, added to risperidone for 8 weeks has been found to significantly improve social functioning (assessed with the social disability screening schedule) in comparison to a placebo [243]. Omega-3 polyunsaturated fatty acids also show potential for beneficial effects on functional outcome, as evidence shows 3-4 months of adjunctive eicosapentaenoic acid treatment to have beneficial effects on psychopathology [244,245].…”
Section: New Approaches To Intervention Programsmentioning
confidence: 96%
“…Similarly, herbal and natural medicines are also in the early phase of testing but have produced some promising results. Warm-supplementing kidney yang, a Chinese herbal medicine, added to risperidone for 8 weeks has been found to significantly improve social functioning (assessed with the social disability screening schedule) in comparison to a placebo [243]. Omega-3 polyunsaturated fatty acids also show potential for beneficial effects on functional outcome, as evidence shows 3-4 months of adjunctive eicosapentaenoic acid treatment to have beneficial effects on psychopathology [244,245].…”
Section: New Approaches To Intervention Programsmentioning
confidence: 96%
“…The ayurvedic group had less weight gain ( Mundewadi et al, 2008 ). Two large studies by Chen et al (2008a , 2008b , 2009) of a mixture of 13 Chinese herbs found an improvement on general psychopathology. When kidney yang was added to risperidone, an improvement on cognitive and depressive symptoms was found in one study (from two) ( Chen et al, 2008a , 2009 ).…”
Section: Reviewmentioning
confidence: 98%
“…Many studies on Eastern herbs were found, but only six had a Jadad score of three or higher ( Chen et al, 2008a , 2008b , 2009 ; Mahal et al, 1976 ; Mundewadi et al, 2008 ; Naidoo, 1956 ). One old study on reserpine found “clinical improvement” after 11 weeks compared with placebo in 80 patients not treated with antipsychotics but with electroconvulsice therapy ( Naidoo, 1956 ).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbal prescriptions, such as WSKY or strong kidney yin, are considered to improve deficits associated with schizophrenia. Previously, it was reported that WSKY capsules in addition to risperidone significantly enhanced cognitive function, social function (6) and improved the quality of life (7) compared with the placebo added to risperidone. The present study focused on the mechanisms underlying WSKY's effects on cognition enhancement.…”
Section: Introductionmentioning
confidence: 99%